A push–pull strategy for controlling the tea green leafhopper (Empoasca flavescens F.) using semiochemicals from Tagetes erecta and Flemingia macrophylla. Issue 6 (12th March 2022) - Niu, Yuqun; Han, Shanjie; Wu, Zihui; Pan, Cheng; Wang, Mengxin; Tang, Yanyan; Zhang, Qing‐He; Tan, Genjia; Han, Baoyu
Abstract: BACKGROUND: The tea green leafhopper, Empoasca flavescens is the most important pest in Chinese tea plantations. For decades its control has been executed almost exclusively through pesticide applications. A semiochemical‐based 'push–pull' strategy was tested on the leafhopper in the study. RESULTS: The odors released from Tagetes erecta and Flemingia macrophylla significantly repelled and attracted leafhoppers, respectively. These volatile compounds (46 from T. erecta and 53 F. macrophylla ) were identified and quantified via gas chromatography–mass spectometry (GC–MS) analysis. Y‐tube olfactometer assays indicated that thymol anisole, thymol and camphor had significant repellent effects on the leafhoppers, resulting in a ternary repellent blend at a 4:3:13 ratio. Cis ‐3‐hexen‐1‐ol, cis ‐3‐hexenyl acetate, nonanal and α ‐farnesene were significantly attractive to the leafhoppers, making an attractant blend at a 17:4:1:1 ratio. In the field, the push–pull strategy with the repellent dispensers placed within the tea bushes and the attractant‐baited sticky traps hung 15 cm above the tea plants showed a significant control efficacy, reaching 69% and 55% at two and 14 days post‐treatment, respectively, similar to those in the insecticide control plots. Additionally, the leafhopper density in the push–pull intercropping plot was 63.2 leafhoppers/100 tea shoots/visit, much lower than those in the pull intercropping plot and nonintercropping plot. CONCLUSION: Application of the push–pull strategy using both synthetic repellent and attractant, or intercropping T. erecta and F. macrophylla with tea plants, can effectively reduce the leafhopper population. This approach might have great potential as an environmentally safe control strategy against the leafhopper. © 2022 Society of Chemical Industry. Abstract : Application of the 'push‐pull' strategy using both synthetic repellent and attractant, or intercropping Tagetes erecta and Flemingia macrophylla with tea plants, can effectively reduce the leafhopper population. This approach might have a great potential as an environmentally safe and green control strategy against the leafhopper.